Pendidikan Politik dalam Pencegahan Politik Uang Melalui Gerakan Masyarakat Desa - Pahlevi, Moch Edward Trias; Amrurobbi, Azka Abdi (Komisi Pemberantasan Korupsi, 2020)
This study explains related to political education in preventing the practice of money politics. The practice of money politics will create corruption and harmful to society. This research used qualitative methods. The results of this study are: first, political education with pre-emtive concept, where the village community declares Anti-Political Money Village in 34 Villages in Special Region of Yogyakarta. Conduct political education ahead of the 2019 elections which is considered effective because people understand that money politics is part of bribery. Second, political education with a preventive concept. The Anti-Money Politics Village Team opens a complaints center for people who witnessed or conducted money politics transactions. These efforts provide social sanctions for bribes.